A 31-day time to surgery compliant exercise training programme improves aerobic health in the elderly - Boereboom, C.L.; Phillips, B.E.; Williams, J.P.; Lund, Jonathan N. (Springer, 2016)
Background: Over 41,000 people were diagnosed with colorectal cancer (CRC) in the UK in 2011. The incidence of CRC increases with age. Many elderly patients undergo surgery for CRC, the only curative treatment. Such patients are exposed to risks, which increase with age and reduced physical fitness. Endurance-based exercise training programmes can improve physical fitness, but such programmes do not comply with the UK, National Cancer Action Team 31-day time-to-treatment target. High-intensity interval training (HIT) can improve physical performance within 2–4 weeks, but few studies have shown HIT to be effective in elderly individuals, and those who do employ programmes longer than 31 days. Therefore, we investigated whether HIT could improve cardiorespiratory fitness in elderly volunteers, age-matched to a CRC population, within 31 days. Methods: This observational cohort study recruited 21 healthy elderly participants (8 male and 13 female; age 67 years (range 62–73 years)) who undertook cardiopulmonary exercise testing before and after completing 12 sessions of HIT within a 31-day period. Results: Peak oxygen consumption (VO2 peak) (23.9 ± 4.7 vs. 26.2 ± 5.4 ml/kg/min, p = 0.0014) and oxygen consumption at anaerobic threshold (17.86 ± 4.45 vs. 20.21 ± 4.11 ml/kg/min, p = 0.008) increased after HIT. Conclusions: It is possible to improve cardiorespiratory fitness in 31 days in individuals of comparable age to those presenting for CRC surgery.